Istiqra Al Ma'nawiy's Reasoning: As a Model of Indigenzation and Contextualization of Islamic Law (Hazairin and Hasbi Ash Shiddiqiy's Thought) - Isman; Risdayani (al-Afkar, Journal For Islamic Studies, 2024)
This paper examines Asy Syatibi's legal reasoning of istiqra al-ma'nawy (thematic induction) and its impact on Indonesia's indigenization and contextualization of Islamic law. The reasoning model of Istiqra al-Ma'nawy Asy Syatibi was the study's first focus. Hazairin and Hasbi Ash Shiddiqiey are efforts to indigenize and contextualize Islam through the use of Istiqra al-Ma'nawy's method in Islamic legal reasoning. Doctrinal or normative legal research with a philosophical viewpoint A documentation model is used to collect data. This study's analytical method uses interpretive, idealistic, and holistic meta-logic. The notion of "natural law" from Islamic and customary law was applied to assess the facts. This study found that istiqra al-ma'nawy Asy Syatibi's reasoning formulation is based on a maslahah approach-based interpretation model, its idealization model is oriented toward text and context integration (tahqiq al-manath), and its holistic model is operationalized hierarchically from the top down (min al-a'la ila al-adna) and from the bottom up (min al-adna ila al-a'la). The integration and connectivity between anthropological studies of the bilateral kinship system of most Indonesian races and Asy Syatibi's legal reasoning influenced Hazairin's indigenization and contextualization of Islam. Hazairin abstracts the universal ideals in the Islamic system of inheritance via istiqra al-ma'nawy. Istiqra al-ma'nawy was used by Hasbi ash Shiddiqiey to reconcile puritanism and contextualism. The Istiqra al-Ma'nawi method strikes a balance between how law is defined (hukm taklify) and how law is made.